1975
DOI: 10.1126/science.189.4201.455
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation: Its Acidic Nature

Abstract: A comparison of the free hydrogen ion concentration and the total hydrogen ion concentration of rain samples shows that rain is a weak acid. The weak acid nature of rain casts doubt on the concepts that the acidity of rain is increasing and that these increases are due to strong acids such as sulfuric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1976
1976
1990
1990

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…When two samples with relatively high pH levels are excluded, the average contribution of free acidity is increased to 81% of the total (27). In comparison, Frohliger and Kane (35) concluded that acid precipitation was caused by unidentified weak acids, but they titrated samples in a vessel open to the atmosphere, and their titrations apparently reflected absorption of CO2 between the atmosphere and the water sample (36). Our results agree well with those of Galloway et al (36) and confirm the hypothesis that acid rainfall is mainly caused by strong acids.…”
Section: Resultssupporting
confidence: 90%
“…When two samples with relatively high pH levels are excluded, the average contribution of free acidity is increased to 81% of the total (27). In comparison, Frohliger and Kane (35) concluded that acid precipitation was caused by unidentified weak acids, but they titrated samples in a vessel open to the atmosphere, and their titrations apparently reflected absorption of CO2 between the atmosphere and the water sample (36). Our results agree well with those of Galloway et al (36) and confirm the hypothesis that acid rainfall is mainly caused by strong acids.…”
Section: Resultssupporting
confidence: 90%
“…A portion of this weak acidity probably was due to the presence of carbonic acid because decreases in total acidity of 15 to 25% were found after removal of volatile gases by bubbling N2 gas through rain samples. Frohliger and Kane (1975) found ratios of 2 to 100 for rainfall in a rural area of Pennsylvania and have interpreted this to mean that strong acids do not play a major role in determining the pH of rainwater. The ratios of total to free H ions for precipitation in Yonkers ranged from 1.2 to 2.9 (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports from the United States claim that weak acids make up a major part of the acids in acid precipitation [37]. When the sample contains weak acids, the buffering capacity of these acids has to be taken into account.…”
Section: Concepts Of Atmospheric Aciditymentioning
confidence: 99%